High-permeability colorimetric hydrogel for detecting glucose content in sweat and preparation method of high-permeability colorimetric hydrogel

By preparing high-permeability colorimetric hydrogels, the catalytic activity of gold-platinum nanoenzyme and the high permeability of the hydrogel are solved, and the existing blood sugar monitoring device is highly costly and complex in operation is achieved, achieving convenient, economical and accurate glucose detection.

CN119708581APending Publication Date: 2025-03-28NINGBO UNIV
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411759807.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-03
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

The existing blood sugar monitoring devices are costly, the electrochemical sensing method requires carrying batteries and analytical and detection elements, and the operation is complex, which limits the application of wearable hydrogels in the continuous health monitoring of glucose.

Method used

Using a high-permeability colorimetric hydrogel, a high-permeability colorimetric hydrogel was prepared by mixing polyoxyethylene polyoxypropylene ether, chloroplatinic acid, tetrachloroauric acid with water, and adding L-ascorbic acid to obtain gold-platinum nanocrystalline nanocrystalline hydrogel for detecting glucose content in sweat. After curing and dialysis of sodium chloride solution, a high-permeability colorimetric hydrogel was prepared.

Benefits of technology

It realizes glucose detection with simple operation, no analysis and detection elements, and low preparation cost. Through the tandem biological enzyme activity of gold-platinum nanoenzyme and the high permeability of hydrogel, sweat absorption efficiency and detection accuracy are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119708581A_ABST
    Figure CN119708581A_ABST
Patent Text Reader

Abstract

The invention provides high-permeability colorimetric hydrogel for detecting the content of glucose in sweat and a preparation method of the high-permeability colorimetric hydrogel, and relates to the technical field of wearable colorimetric sensing. The preparation method of the high-permeability colorimetric hydrogel comprises the following steps: mixing polyoxyethylene polyoxypropylene ether, chloroplatinic acid, chloroauric acid and water, and then adding L-ascorbic acid for reaction to obtain gold-platinum nanocrystalline dendrites; the preparation method comprises the following steps: mixing polyvinyl alcohol, 3, 3 ', 5, 5'-tetramethyl benzidine, gold-platinum nanocrystalline dendrites, ethylene glycol and water to obtain a hydrogel precursor solution, and curing the hydrogel precursor solution to obtain a hydrogel precursor; and soaking the hydrogel precursor in a sodium chloride solution to obtain the high-permeability colorimetric hydrogel for detecting the content of glucose in sweat. The gold-platinum nanocrystal dendrite nanoenzyme has tandem bio-enzyme activity, glucose oxidase activity and peroxidase double-enzyme activity, and TMB is used as a chromogenic substrate to prepare the hydrogel, so that colorimetric detection of glucose can be realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of wearable colorimetric sensing, and in particular to a high-permeability colorimetric hydrogel for detecting glucose content in sweat and a preparation method thereof. Background Art

[0002] Diabetes is an incurable chronic disease that causes tissue damage and metabolic disorders such as cardiovascular disease, kidney damage, nerve damage and retinopathy. According to the different causes and pathogenesis, it can be divided into two main types: type 1 and type 2. Type 2 is often associated with obesity, lack of exercise and bad living habits. At present, the more accurate measurement method is the biochemical test of blood in the hospital. However, this method is not convenient for people with a fast-paced life. It is limited by time and space and cannot monitor and analyze the health status of individuals in real time. In recent years, portable devices such as blood glucose meters and continuous glucose monitors (CGMs) have been commercialized. Their small and portable features are favored by people, but they are expensive. Minimally invasive and invasive testing will bring long-term fingertip blood collection shadows to patients. Therefore, a convenient, efficient and non-invasive health monitoring method is needed to meet the needs of more people. Wearable hydrogel is an emerging material with the characteristics of softness, lightness and high water content. It is usually composed of polymer matrix and water. The unique properties of this material have made it widely used in many fields such as medicine, electronics and bioengineering. In recent years, researchers have combined hydrogels with electrochemical sensors, using gel to extract sweat or gel microneedles to extract interstitial fluid, and then glucose is catalyzed into hydrogen peroxide by glucose oxidase, and then catalyzed by horseradish catalase, and the generated electrical signal is used to quantify the glucose content in biological fluids. It is reported that the glucose content in human sweat or interstitial fluid has a certain correlation with blood sugar. Therefore, this method can solve the above-mentioned invasive and time and geographical limitations. Problems. However, the electrochemical sensing method requires carrying batteries, analysis and detection elements, and requires professional laboratory technicians to complete the operation. In addition, biological enzymes are expensive, difficult to screen, and require suitable reaction conditions to achieve the optimal catalytic effect. These greatly limit the application of wearable hydrogels in continuous health monitoring of glucose. Therefore, the art urgently needs to disclose a wearable hydrogel for detecting the glucose content in sweat that is simple to operate, does not require analysis and detection elements, and has low preparation cost. Summary of the invention

[0003] The purpose of the present invention is to provide a high permeability colorimetric hydrogel for detecting the glucose content in sweat and a preparation method thereof, so as to solve the problems of high cost, electrochemical sensing method requiring batteries and analysis and detection elements, and complex operation of existing blood glucose monitoring devices.

[0004] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0005] The present invention provides a method for preparing a high permeability colorimetric hydrogel for detecting glucose content in sweat, comprising the following steps:

[0006] 1) mixing polyoxyethylene polyoxypropylene ether, chloroplatinic acid, tetrachloroauric acid and water, and then adding L-ascorbic acid to react to obtain gold-platinum nanocrystal dendrites;

[0007] 2) mixing polyvinyl alcohol, 3,3',5,5'-tetramethylbenzidine, gold platinum nanocrystals, ethylene glycol and water to obtain a hydrogel precursor solution, and curing the hydrogel precursor solution to obtain a hydrogel precursor;

[0008] 3) Soaking the hydrogel precursor in a sodium chloride solution to obtain a high permeability colorimetric hydrogel for detecting the glucose content in sweat.

[0009] Preferably, in step 1), the addition ratio of the polyoxyethylene polyoxypropylene ether, chloroplatinic acid, tetrachloroauric acid, ascorbic acid and water is 40-80 mg: 0.02-0.04 mmol: 0.02-0.04 mmol: 0.2-0.7 mmol: 4 mL.

[0010] Preferably, the reaction temperature in step 1) is 20-30° C., and the reaction time is 15-24 h.

[0011] Preferably, in the hydrogel precursor solution in step 2), the mass concentration of polyvinyl alcohol is 3-4wt%, the mass concentration of 3,3',5,5'-tetramethylbenzidine is 0.1-0.2wt%, and the mass concentration of gold platinum nanocrystal dendrites is 0.2-0.4wt%;

[0012] The mass ratio of the ethylene glycol to water is 1 to 4:1.

[0013] Preferably, the solidification in step 2) is to freeze-thaw the hydrogel precursor solution in a cycle;

[0014] The number of cycles is 2 to 4 times.

[0015] Preferably, the freezing temperature is -20 to 0°C and the freezing time is 4 to 8 hours;

[0016] The melting temperature is 20-30° C., and the melting time is 1-2 hours.

[0017] Preferably, the thickness of the hydrogel precursor in step 2) is 1 to 1.5 mm.

[0018] Preferably, the concentration of the sodium chloride solution in step 3) is 1 to 5 mol / L, and the pH value is 6 to 7;

[0019] The soaking time is 6 to 8 hours.

[0020] The present invention also provides a high permeability colorimetric hydrogel prepared by the above preparation method and used for detecting the glucose content in sweat.

[0021] The present invention has at least the following beneficial effects:

[0022] The wearable high-permeability colorimetric hydrogel of the present invention uses polyvinyl alcohol as a precursor, gold platinum nanocrystal dendrites (AuPtNDs) nanozyme as a catalytic medium, and TMB as a color-developing substrate to heat and form a hydrogel. The osmotic pressure of the hydrogel is increased by dialysis with a sodium chloride solution, which works together with the capillary force of the hydrogel to improve the efficiency of absorbing sweat. The AuPtNDs nanozyme has tandem biological enzyme activity, both glucose oxidase activity and peroxidase dual enzyme activity. Only a single nanozyme can be used to achieve colorimetric detection of glucose. This catalytic performance is brought about by its branched nanostructure, and the preparation method of the nanozyme is simple, low-cost, and less affected by temperature and pH, which is conducive to promotion and use. As a precursor of hydrogel, polyvinyl alcohol material has strong water absorption, biocompatibility and mechanical properties, and can fit the skin perfectly. After being infiltrated by sodium chloride solution, the hydrogel increases its osmotic pressure under the action of the original capillary force, greatly improving the efficiency of hydrogel in extracting sweat. It can effectively allow water and small molecules to pass through, and realize the monitoring of glucose content in sweat during rest. After adding ethylene glycol to polyvinyl alcohol hydrogel, the mechanical strength and optical transmittance of the material can also be improved. The test results can be obtained by reading the RGB value by the naked eye or a smartphone. The operation is simple and quick, and does not require professional experimenters to operate. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 This is a picture of the high permeability colorimetric hydrogel prepared in Example 1 of the present invention for detecting the glucose content in sweat. Figure 1 a in the figure is an optical photograph of a high permeability colorimetric hydrogel. Figure 1 b is a scanning electron micrograph of a high permeability colorimetric hydrogel;

[0024] Figure 2 Optical images of the front and side surfaces of the high permeability colorimetric hydrogel for detecting glucose content in sweat prepared in Example 1 of the present invention. Figure 2 a in the figure is a frontal photo of the high permeability colorimetric hydrogel. Figure 2 b is a side view of the high permeability colorimetric hydrogel;

[0025] Figure 3The optical images of the high permeability colorimetric hydrogel prepared in this example for detecting the glucose content in sweat when subjected to operations such as lifting, stretching, twisting, and folding, indicate that the hydrogel has good mechanical properties;

[0026] Figure 4 This is a diagram showing the color changes of the high permeability colorimetric hydrogel for detecting the glucose content in sweat prepared in Example 1 of the present invention under the action of different glucose concentrations;

[0027] Figure 5 This is a curve showing the change of RGB value of the high permeability colorimetric hydrogel for detecting glucose content in sweat prepared in Example 1 of the present invention with the concentration of glucose solution;

[0028] Figure 6 This is a schematic diagram of actually measuring the glucose concentration in human sweat using the high permeability colorimetric hydrogel prepared in Example 1 of the invention for detecting the glucose content in sweat. Figure 6 Figure a is a schematic diagram of the hydrogel attached to the volunteer's arm. Figure 6 Figure b is an optical photo of the hydrogel before it was attached to the volunteer's arm. Figure 6 The c in the figure is an optical photo of the hydrogel after it was attached to the volunteer's arm for 15 minutes and then removed. Figure 6 The d in the figure is the result of blood glucose test on volunteers using a blood glucose meter;

[0029] Figure 7 The highly permeable colorimetric hydrogel prepared in Examples 1 to 3 for detecting the glucose content in sweat, and the statistical graph of the weight change of the hydrogel before and after the hydrogel precursor described in step (2) of Example 1 is attached to the surface of agarose gel with a glucose concentration of 1.5 wt%. DETAILED DESCRIPTION

[0030] The present invention provides a method for preparing a high permeability colorimetric hydrogel for detecting glucose content in sweat, comprising the following steps:

[0031] 1) mixing polyoxyethylene polyoxypropylene ether, chloroplatinic acid, tetrachloroauric acid and water, and then adding L-ascorbic acid to react to obtain gold-platinum nanocrystal dendrites;

[0032] 2) mixing polyvinyl alcohol, 3,3',5,5'-tetramethylbenzidine, gold platinum nanocrystals, ethylene glycol and water to obtain a hydrogel precursor solution, and curing the hydrogel precursor solution to obtain a hydrogel precursor;

[0033] 3) Soaking the hydrogel precursor in a sodium chloride solution to obtain a high permeability colorimetric hydrogel for detecting the glucose content in sweat.

[0034] In the present invention, the addition ratio of the polyoxyethylene polyoxypropylene ether, chloroplatinic acid, tetrachloroauric acid, ascorbic acid and water in step 1) is 40-80 mg: 0.02-0.04 mmol: 0.02-0.04 mmol: 0.2-0.7 mmol: 4 mL, preferably 45-75 mg: 0.025-0.035 mmol: 0.025-0.035 mmol: 0.3-0.6 mmol: 4 mL, further preferably 50-70 mg: 0.028-0.032 mmol: 0.028-0.032 mmol: 0.4-0.5 mmol: 4 mL, and more preferably 55-60 mg: 0.03 mmol: 0.03 mmol: 0.45 mmol: 4 mL.

[0035] In the present invention, the reaction temperature in step 1) is 20-30°C, preferably 22-28°C, more preferably 24-26°C, and more preferably 25°C; the reaction time is 15-24h, preferably 17-22h, and more preferably 18-20h.

[0036] In the present invention, the method of mixing the polyoxyethylene polyoxypropylene ether, chloroplatinic acid, tetrachloroauric acid and water in step 1) is preferably to first prepare the polyoxyethylene polyoxypropylene ether, chloroplatinic acid and tetrachloroauric acid into solutions respectively, then mix them and perform ultrasonic treatment for 5 to 10 minutes.

[0037] In the present invention, after adding ascorbic acid in step 1), the mixture needs to be precipitated at room temperature for 20 to 24 hours. During the precipitation process, it needs to be left to stand to allow the dendrites to grow, and the color of the solution changes from yellow to dark black. After the precipitation is completed, the step of separating and purifying the gold-platinum nanocrystal dendrites is also included, specifically, centrifuging at a speed of 7500r / min for 5 minutes, circulating twice, and finally resuspending the gold-platinum nanocrystal dendrites in a CTAB (hexadecyltrimethylammonium bromide) solution, the volume of the CTAB solution is 1mL, and the concentration is 50mmol / L.

[0038] In the present invention, the mass concentration of polyvinyl alcohol in the hydrogel precursor solution in step 2) is 3-4wt%, preferably 3.2-3.8wt%, more preferably 3.4-3.6wt%, and more preferably 3.5wt%; the mass concentration of 3,3',5,5'-tetramethylbenzidine is 0.1-0.2wt%, preferably 0.12-0.18wt%, more preferably 0.14-0.16wt%, and more preferably 0.15wt%; the mass concentration of gold platinum nanocrystal dendrites is 0.2-0.4wt%, preferably 0.23-0.38wt%, more preferably 0.25-0.35wt%, and more preferably 0.28-0.30wt%.

[0039] In the present invention, the mass ratio of ethylene glycol to water is 1 to 4:1, preferably 1.5 to 3.5:1, more preferably 2 to 3:1, and more preferably 2.5:1.

[0040] In the present invention, the mixing temperature in step 2) is 90-100°C, preferably 92-98°C, and more preferably 95°C.

[0041] In the present invention, the solidification is to freeze and melt the hydrogel precursor solution cyclically for 2 to 4 times until the hydrogel precursor solution forms a gel;

[0042] Polyvinyl alcohol needs to go through a freezing and melting process to become a gel. The specific mechanism is as follows:

[0043] Freezing stage: When the polyvinyl alcohol aqueous solution is frozen, the water will form ice crystals, and the polyvinyl alcohol molecules will be "pressed" between the ice crystals, thereby promoting contact between molecules. Due to the low mobility of the polyvinyl alcohol molecules in the low temperature environment, hydrogen bonds between the molecules gradually begin to form.

[0044] Melting stage: During the melting process, the water phase will turn into liquid again, and the polyvinyl alcohol molecules will gain a certain degree of freedom. The hydrogen bonds and interactions formed at this time maintain a certain network structure, so that the solution gradually turns into a gel.

[0045] In the present invention, the freezing temperature is -20 to 0°C, preferably -18 to -3°C, more preferably -15 to -5°C, and more preferably -13 to -8°C; the freezing time is 4 to 8h, preferably 5 to 7h, and more preferably 6h.

[0046] In the present invention, the melting temperature is 20 to 30° C., preferably 22 to 28° C., and more preferably 25° C.; the melting time is 1 to 2 hours.

[0047] In the present invention, the thickness of the hydrogel precursor in step 2) is 1 to 1.5 mm, preferably 1.1 to 1.4 mm, and more preferably 1.2 to 1.3 mm.

[0048] In the present invention, the concentration of the sodium chloride solution in step 3) is 1-5 mol / L, preferably 2-4.5 mol / L, more preferably 3-4 mol / L, more preferably 3.5 mol / L; the pH value is 6-7, preferably 6.2-6.8, more preferably 6.4-6.6, more preferably 6.5.

[0049] In the present invention, the soaking time is 6 to 8 hours, preferably 6.5 to 7.5 hours, and more preferably 7 hours.

[0050] The present invention also provides a high permeability colorimetric hydrogel prepared by the above preparation method and used for detecting the glucose content in sweat.

[0051] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.

[0052] Example 1

[0053] (1) At room temperature, 60 mg of pluronic F-127 (polyoxyethylene polyoxypropylene ether, Shanghai Biyuntian Biotechnology Co., Ltd.) was completely dissolved in 2 mL of distilled water, and then chloroplatinic acid solution (0.5 mL, 100 mmol / L) and tetrachloroauric acid solution (0.5 mL, 100 mmol / L) were added. After the mixture was ultrasonically treated for 1 min, L-ascorbic acid solution (1 mL, 0.25 mol / L) was added to the reaction mixture. The mixture was allowed to settle at room temperature for 1 day to allow dendrites to grow, during which the solution color changed from yellow to dark black. After standing, the mixed product was centrifuged and purified at room temperature (7500 rpm, 5 minutes, 2 cycles, detergent was water) to obtain gold platinum nanoparticles (AuPtNDs) dendrites, which were finally resuspended in CTAB (1 mL, 50 mmol / L).

[0054] (2) Mix 5.76g of ethylene glycol, 3.98g of distilled water and 0.4g of polyvinyl alcohol (1799 type), then add TMB (100uL, 10mmol / L) and AuPtNDs dendrites (50uL, 50mmol / L), and stir the mixture vigorously at 95°C for 3h until all reagents are dissolved to obtain a hydrogel precursor solution. Preheat the mold (24-well plate, watch glass, glass bottle) at 65°C for 5min, and use a pipette to draw the hydrogel precursor solution into the mold to control the gel thickness to 1.5mm. After cooling to room temperature, put it in a refrigerator at -20°C and freeze it for 6h, then take it out, and then thaw it at room temperature for 2h. Repeat freezing and thawing three times to obtain a hydrogel precursor.

[0055] (3) The obtained hydrogel was taken out from the 24-well plate and then immersed in a 5 mol / L sodium chloride solution (pH=6) to adjust the pH and osmotic pressure. After immersion for 8 hours, the hydrogel was taken out and the surface was washed with deionized water to obtain a high permeability colorimetric hydrogel for detecting the glucose content in sweat, which was wrapped with plastic wrap and stored at 4°C for use.

[0056] Figure 1 This is a picture of the high permeability colorimetric hydrogel prepared in this example for detecting the glucose content in sweat. Figure 1 a in the figure is an optical photograph of a high permeability colorimetric hydrogel. Figure 1 b is a scanning electron micrograph of a high permeability colorimetric hydrogel. Figure 1 From b, we can see that the hydrogel has a porous structure.

[0057] Figure 2 Optical images of the front and side surfaces of the high permeability colorimetric hydrogel prepared in this example for detecting glucose content in sweat. Figure 2 a in the figure is a frontal photo of the high permeability colorimetric hydrogel. Figure 2 b is a side view of the high permeability colorimetric hydrogel. Figure 2 It can be seen that the hydrogel has good optical transmittance.

[0058] Figure 3 In order to introduce the high permeability colorimetric hydrogel prepared in this example for detecting the glucose content in sweat ( Figure 3 a), stretching ( Figure 3 b), distortion ( Figure 3 c), folding ( Figure 3 The optical images during operations such as (d) in the figure indicate that the hydrogel has good mechanical properties.

[0059] Example 2

[0060] The only difference from Example 1 is that the concentration of the sodium chloride solution used is 1 mol / L, and the remaining steps are the same as those in Example 1.

[0061] Example 3

[0062] The only difference from Example 1 is that the concentration of the sodium chloride solution used is 3 mol / L, and the remaining steps are the same as those in Example 1.

[0063] The hydrogel prepared in Example 1 was immersed in glucose solutions of different concentrations (concentration gradient: 0mmol / L, 1mmol / L, 3mmol / L, 5mmol / L, 10mmol / L, 15mmol / L) for 15 min, and its color change was observed. The photos were taken with a mobile phone (shooting parameters were ISO: 3200, S: 1 / 200). The results are as follows: Figure 4 As shown in Table 1, the color of the hydrogel becomes darker as the glucose concentration increases. The RGB values ​​of the hydrogel (RGB values ​​refer to the values ​​of red, green and blue) are further analyzed. The specific data are shown in Table 1. Figure 5 The curve of hydrogel RGB value changing with glucose solution concentration is shown in Figure 2. Figure 5 It can be seen that the trend of G and B values ​​changing with concentration is not as large as that of R value. Therefore, in the actual detection process, we choose R value for quantification.

[0064] Example 4

[0065] (1) At room temperature, 40 mg of pluronic F-127 (polyoxyethylene polyoxypropylene ether, Shanghai Biyuntian Biotechnology Co., Ltd.) was completely dissolved in 2.3 mL of distilled water, and then chloroplatinic acid solution (0.3 mL, 100 mmol / L) and tetrachloroauric acid solution (0.4 mL, 100 mmol / L) were added. After the mixture was ultrasonically treated for 1 min, L-ascorbic acid solution (1 mL, 0.25 mol / L) was added to the reaction mixture. The mixture was allowed to settle at room temperature for 1 day to allow dendrites to grow, during which the color of the solution changed from yellow to dark black. After standing, the mixed product was centrifuged and purified at room temperature (7500 rpm, 5 minutes, 3 cycles, detergent was water) to obtain gold platinum nanoparticles (AuPtNDs) dendrites, which were finally resuspended in CTAB (1 mL, 50 mmol / L).

[0066] (2) Mix 8g ethylene glycol, 4g distilled water and 0.5g polyvinyl alcohol (1799 type), then add TMB (100uL, 10mmol / L) and AuPtNDs dendrites (50uL, 50mmol / L), and stir the mixture vigorously at 95°C for 3h until all reagents are dissolved to obtain a hydrogel precursor solution. Preheat the mold (24-well plate, watch glass, glass bottle) at 65°C for 5min, and use a pipette to draw the hydrogel precursor solution into the mold to control the gel thickness to 1.5mm. After cooling to room temperature, put it in a refrigerator at -20°C and freeze it for 6h, then take it out, and then thaw it at room temperature for 2h. Repeat freezing and thawing three times to obtain a hydrogel precursor.

[0067] (3) The obtained hydrogel was taken out from the 24-well plate and then immersed in a 5 mol / L sodium chloride solution (pH=6) to adjust the pH and osmotic pressure. After immersion for 8 hours, the hydrogel was taken out and the surface was washed with deionized water to obtain a high permeability colorimetric hydrogel for detecting the glucose content in sweat, which was wrapped with plastic wrap and stored at 4°C for use.

[0068] Example 5

[0069] (1) At room temperature, 80 mg of pluronic F-127 (polyoxyethylene polyoxypropylene ether, Shanghai Biyuntian Biotechnology Co., Ltd.) was completely dissolved in 2 mL of distilled water, and then chloroplatinic acid solution (0.5 mL, 100 mmol / L) and tetrachloroauric acid solution (0.2 mL, 100 mmol / L) were added. After the mixture was ultrasonically treated for 1 min, L-ascorbic acid solution (0.4 mL, 0.25 mol / L) was added to the reaction mixture. The mixture was allowed to stand at room temperature for 1 day to allow dendrites to grow, during which the solution color changed from yellow to dark black. After standing, the mixed product was centrifuged and purified at room temperature (7500 rpm, 5 minutes, 2 cycles, detergent was water) to obtain gold platinum nanoparticles (AuPtNDs) dendrites, which were finally resuspended in CTAB (1 mL, 50 mmol / L).

[0070] (2) Mix 7.8g ethylene glycol, 1.95g distilled water and 0.44g polyvinyl alcohol (1799 type), then add TMB (100uL, 10mmol / L) and AuPtNDs dendrites (50uL, 50mmol / L), and stir the mixture vigorously at 95°C for 3h until all reagents are dissolved to obtain a hydrogel precursor solution. Preheat the mold (24-well plate, watch glass, glass bottle) at 65°C for 5min, and use a pipette to draw the hydrogel precursor solution into the mold to control the gel thickness to 1.5mm. After cooling to room temperature, put it in a refrigerator at -20°C and freeze it for 6h, then take it out, and then thaw it at room temperature for 2h. Repeat freezing and thawing three times to obtain a hydrogel precursor.

[0071] (3) The obtained hydrogel was taken out from the 24-well plate and then immersed in a 5 mol / L sodium chloride solution (pH=6) to adjust the pH and osmotic pressure. After immersion for 8 hours, the hydrogel was taken out and the surface was washed with deionized water to obtain a high permeability colorimetric hydrogel for detecting the glucose content in sweat, which was wrapped with plastic wrap and stored at 4°C for use.

[0072] Table 1 RGB values ​​of the high permeability colorimetric hydrogel prepared in Example 1 after being immersed in glucose solutions of different concentrations

[0073]

[0074] Wipe the volunteer's skin dry with alcohol, take the hydrogel out of the refrigerator, and peel off the sealing layer; stick the hydrogel on the volunteer's palm, forehead, etc., wait for 15 minutes, and then use a mobile phone combined with color picking software to perform RGB value quantitative analysis. Finally, the test can be completed and the results can be obtained after analysis. Figure 6 , which is a schematic diagram of the color change of the high permeability colorimetric hydrogel for detecting the glucose content in sweat prepared in Example 1 before and after being attached to the arm of a volunteer, Figure 6Figure a is a schematic diagram of the hydrogel attached to the volunteer's arm. Figure 6 Figure b is an optical photo of the hydrogel before it was attached to the volunteer's arm. Figure 6 The c in the figure is an optical photo of the hydrogel after it was attached to the volunteer's arm for 15 minutes and then removed. Figure 6 The d in the figure is the result of blood glucose test on volunteers using a blood glucose meter.

[0075] Figure 7 The highly permeable colorimetric hydrogels prepared in Examples 1 to 3 for detecting the glucose content in sweat, and the weight change statistics of the hydrogels before and after the hydrogel precursor described in step (2) of Example 1 was attached to the surface of an agarose gel with a glucose concentration of 1.5 wt %. The attachment time was 15 min. Figure 7 It can be seen that as the concentration of the sodium chloride solution used for immersion increases, the ability of the high osmotic colorimetric hydrogel to extract the solution increases, and the mass difference before and after adsorption becomes larger.

[0076] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing a high permeability colorimetric hydrogel for detecting glucose content in sweat, characterized in that: The following steps are involved: 1) mixing polyoxyethylene polyoxypropylene ether, chloroplatinic acid, tetrachloroauric acid and water, and then adding L-ascorbic acid to react to obtain gold-platinum nanocrystal dendrites; 2) mixing polyvinyl alcohol, 3,3',5,5'-tetramethylbenzidine, gold platinum nanocrystals, ethylene glycol and water to obtain a hydrogel precursor solution, and curing the hydrogel precursor solution to obtain a hydrogel precursor; 3) Soaking the hydrogel precursor in a sodium chloride solution to obtain a high permeability colorimetric hydrogel for detecting the glucose content in sweat.

2. The method for preparing a high permeability colorimetric hydrogel for detecting glucose content in sweat according to claim 1, characterized in that: The addition ratio of the polyoxyethylene polyoxypropylene ether, chloroplatinic acid, tetrachloroauric acid, ascorbic acid and water in step 1) is 40-80 mg: 0.02-0.04 mmol: 0.02-0.04 mmol: 0.2-0.7 mmol: 4 mL.

3. The method for preparing a high permeability colorimetric hydrogel for detecting glucose content in sweat according to claim 2, characterized in that: The reaction temperature in step 1) is 20-30° C., and the reaction time is 15-24 h.

4. The method for preparing a high permeability colorimetric hydrogel for detecting glucose content in sweat according to any one of claims 1 to 3, characterized in that: In step 2), the mass concentration of polyvinyl alcohol in the hydrogel precursor solution is 3-4wt%, the mass concentration of 3,3',5,5'-tetramethylbenzidine is 0.1-0.2wt%, and the mass concentration of gold platinum nanocrystal dendrites is 0.2-0.4wt%; The mass ratio of the ethylene glycol to water is 1 to 4:

1.

5. The method for preparing a high permeability colorimetric hydrogel for detecting glucose content in sweat according to claim 4, characterized in that: The solidification in step 2) is to freeze and melt the hydrogel precursor solution in a cycle; The number of cycles is 2 to 4 times.

6. The method for preparing a high permeability colorimetric hydrogel for detecting glucose content in sweat according to claim 5, characterized in that: The freezing temperature is -20 to 0°C, and the freezing time is 4 to 8 hours; The melting temperature is 20-30° C., and the melting time is 1-2 hours.

7. The method for preparing a high permeability colorimetric hydrogel for detecting glucose content in sweat according to claim 5 or 6, characterized in that: The thickness of the hydrogel precursor in step 2) is 1 to 1.5 mm.

8. The method for preparing a high permeability colorimetric hydrogel for detecting glucose content in sweat according to claim 7, characterized in that: The concentration of the sodium chloride solution in step 3) is 1-5 mol / L, and the pH value is 6-7; The soaking time is 6 to 8 hours.

9. A high permeability colorimetric hydrogel for detecting the content of glucose in sweat, prepared by the method for preparing a high permeability colorimetric hydrogel for detecting the content of glucose in sweat as claimed in any one of claims 1 to 8.

Citation Information

Cited By

  • Wearable hydrogel sensor and method for rapidly detecting glucose concentration of sweat

    CN120464123A